LOCALLY CONFORMAL HIGHER ORDER LAGRANGIAN DYNAMICS - Cite, Serdar; Esen, Ogul (Inst Mathematics & Mechanics, Natl Acad Sciences Azerbaijan, 2025)
This work presents higher order Lagrangian dynamics possessing locally conformal character. More concretely, locally conformal higher order Euler-Lagrange equations are written with particular focus on the second-and the third-order cases.
Keywords: Locally conformally symplectic manifolds; higher order Lagrangians; locally conformal Lagrangian theory